Comparative Analysis of Data Visualization Tools: Tableau, Power BI & Looker - Patel, Dip Bharatbhai (Eastasouth Institute, 2023)
Data visualization tools are now becoming common due to the usability and function that they offer in different sectors. We are in the era of big data, which means that the usability that is needed for data visualization to work on the data is growing. Data is a growing part of our lives as there comes the need for understanding, analyzing, visualizing, and being able to use the data, which is key to how it is being used in various sectors.